ANCA Associated Vasculitis Subtypes: Response [Letter] - Merkel PA; Jayne DRW; Bekker P (Dove Medical Press, 2022)
Peter A Merkel,1 David RW Jayne,2 Pirow Bekker3 1University of Pennsylvania, Philadelphia, PA, USA; 2University of Cambridge, Cambridge, England; 3ChemoCentryx Inc, San Carlos, CA, USACorrespondence: Peter A Merkel, Division of Rheumatology, University of Pennsylvania, White Building, Fifth Floor, 3400 Spruce Street, Philadelphia, PA, 19104, USA, Email pmerkel@pennmedicine.upenn.edu